Border conditions : Russian-speaking Latvians between world orders - Platt, Kevin M. F. (2024)
"This book examines the social conditions and literary and cultural life of Russian-speaking residents of Latvia since the collapse of the USSR in 1991. Discussion centers on history and memory of the Russian Empire and the Soviet Union in the Baltic region and tensions between European, Latvian, and Russian frames of reference